PENGEMBANGAN RANTAI NILAI (VALUE CHAIN) EKONOMI KREATIF MELALUI HILIRISASI ENERGI TERBARUKAN DI TINGKAT UMKM MEDAN JOHOR - Muhammad Harpis; Mega Hasibuan; Herlin Simanullang (Jurnal Manajemen Ekonomi dan Bisnis, 2025)
AbstractThis study aims to analyze the development of the creative economy value chain through downstream renewable energy at the Micro, Small, and Medium Enterprises (MSME) level in Medan Johor District. The background of this research is based on the still low integration of renewable energy utilization in MSME production activities, despite the creative economy sector having significant potential to increase product added value through sustainability-based innovation. The research problem formulation in this study is how to develop a creative economy value chain integrated with downstream renewable energy and its impact on increasing MSME competitiveness. The research method uses a qualitative descriptive approach supported by quantitative data. Data collection was conducted through observation, in-depth interviews with MSME creative economy actors, and documentation studies. Data analysis was conducted by mapping the value chain from raw material procurement, production processes, renewable energy utilization, to product distribution and marketing. The research results show that integrating renewable energy, such as the use of small-scale solar panels and biomass, can reduce operational costs, increase production efficiency, and strengthen the image of environmentally friendly products. Downstreaming renewable energy also encourages the creation of innovative, sustainability-based creative products with higher sales value. However, the main obstacles still lie in limited capital, technological literacy, and access to technical assistance. This research confirms that strengthening the creative economy value chain based on renewable energy has the potential to become a strategy for sustainable MSME development at the local level, particularly in Medan Johor, through collaboration between the government, business actors, and supporting institutions. AbstrakPenelitian ini bertujuan menganalisis pengembangan rantai nilai (value chain) ekonomi kreatif melalui hilirisasi energi terbarukan pada tingkat Usaha Mikro, Kecil, dan Menengah (UMKM) di Kecamatan Medan Johor. Latar belakang penelitian ini didasarkan pada masih rendahnya integrasi pemanfaatan energi terbarukan dalam aktivitas produksi UMKM, padahal sektor ekonomi kreatif memiliki potensi besar untuk meningkatkan nilai tambah produk melalui inovasi berbasis keberlanjutan. Rumusan masalah dalam penelitian ini adalah bagaimana model pengembangan rantai nilai ekonomi kreatif yang terintegrasi dengan hilirisasi energi terbarukan serta dampaknya terhadap peningkatan daya saing UMKM. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan dukungan data kuantitatif. Pengumpulan data dilakukan melalui observasi, wawancara mendalam kepada pelaku UMKM ekonomi kreatif, serta studi dokumentasi. Analisis data dilakukan dengan memetakan rantai nilai mulai dari penyediaan bahan baku, proses produksi, pemanfaatan energi terbarukan, hingga distribusi dan pemasaran produk. Hasil penelitian menunjukkan bahwa integrasi energi terbarukan, seperti pemanfaatan panel surya skala kecil dan biomassa, mampu menekan biaya operasional, meningkatkan efisiensi produksi, serta memperkuat citra produk ramah lingkungan. Hilirisasi energi terbarukan juga mendorong terciptanya inovasi produk kreatif berbasis keberlanjutan yang memiliki nilai jual lebih tinggi. Namun, kendala utama masih terletak pada keterbatasan modal, literasi teknologi, dan akses terhadap pendampingan teknis. Penelitian ini menegaskan bahwa penguatan rantai nilai ekonomi kreatif berbasis energi terbarukan berpotensi menjadi strategi pembangunan UMKM berkelanjutan di tingkat lokal, khususnya di Medan Johor, melalui kolaborasi antara pemerintah, pelaku usaha, dan lembaga pendukung.